Time-domain analysis based on the electromechanical impedance method for monitoring of the dressing operation - Conceicao Junior, Pedro Oliveira da [UNESP]; Ferreira, Fabio Isaac [UNESP]; Aguiar, Paulo Roberto de [UNESP]; Batista, Fabricio Guimaraes [UNESP]; Bianchi, Eduardo Carlos [UNESP]; D'Addona, Doriana Marilena; Teti, R.; DAddona, D. M. (Elsevier B.V., 2018)
Among the methods used in structural health monitoring (SHM), the electromechanical impedance technique (EMI), which uses piezoelectric transducers of lead zirconate titanate (PZT), stands out for its low cost. Then, this paper presents a new approach for monitoring of the dressing operation from the digital processing of voltage signals based on the time-domain response of a PZT transducer by EMI method. Experimental tests of the dressing process were performed by using a single-point dresser equipped with a natural diamond. The voltage signals in the time-domain were collected in different damage levels. By using temporal statistics, it was possible to qualify different damage levels that the diamond suffered during the dressing operation, observing variations from the magnitude of the signals. The dressing operation is of utmost importance for the grinding process and the dresser wear negatively affects the result of the process, which owns high added value. In this way, this work contributes with a new monitoring tool which aims ensuring a consistent dressing operation. (C) 2017 The Authors. Published by Elsevier B.V.
Keywords: Manufacturing system; digital signal processing; electromechanical impedance; dressing operation